Socio-personal correlates of participation in livelihood activities among rural youth in Jabalpur district of Madhya pradesh, India (International Journal of Agricultural Research, Innovation and Technology, 2015)
The increasing realization of the negative political, social and economic consequences stemming from the precariousness of youths livelihoods, underscores the need to understand their livelihood activities, which is a requisite for curbing social ills and reducing rural poverty. The paper examined the participation of rural youth in livelihood activities, their socio-personal characteristics, the relationship between their socio-personal characteristics and their participation in livelihood activities as well as the interrelationships among their socio-personal characteristics. Multi-stage random sampling was used to collect data from 247 respondents through interview schedule. Frequency counts and percentages were used to present data while Pearson product moment correction (PPMC) was used to test relationships. The results revealed that majority of the respondents were from other backward caste (66%), married (72.10%), belonged to joint (57.90%) and medium (50.60%) size families as well as families that were self-employed in agriculture (59.50%). Higher percentages of the respondents and their fathers were educated up to higher school and above. Huge majority (75.71%) of the respondents participated in cereal production while more than half of the respondents were involved in pulse production (56.28%) and petty trading (53.44%). Marital status; fathers educational attainment; family type and family size had significant relationship with participation in livelihood activities. Inter-correlations among socio-personal characteristics showed that caste was related to marital status and educational attainment. It is concluded that socio-personal attributes of rural youth are related to their participation in livelihood activities. The study recommends that socio-personal variables of present study be considered by rural development policy makers when undertaking programmes aimed at enhancing rural youths livelihoods.Int. J. Agril. Res. Innov. & Tech. 5 (1): 28-35, June, 2015